PRICE VOLATILITY ANALYZE IN EARLY PANDEMIC COVID 19 OUTBREAKS: CASE STUDY IN GORONTALO PROVINCE SHALLOT MARKET - Yuliana Bakari (Agricultural Socio-Economics Journal, 2023)
The Covid-19 pandemic in early 2020 led to unpredictable price fluctuation in agricultural commodities such as Shallots. The purpose of this research was to analyze the price fluctuation behavior of shallots in Gorontalo Province during the Covid-19 Pandemic and the price volatility surge as well as the effect of the pandemic during 2020. This study used data from The National Food Strategy Information Center in the form of weekly price in time-series from January 2018 to December 2020. The data analysis on price volatility was conducted using the Auto-Regressive Conditional Heteroscedastic and Generalized Auto-Regressive Conditional Heteroscedastic (ARCH / GARCH) Models. The results show that shallot price behavior randomly fluctuates every year, is more unpredictable, and has significant fluctuation over 2020. The ARCH / GARCH models prove that Pandemic Covid-19 in 2020 triggered the unpredictable price fluctuation and led to price volatility of shallots commodity in Gorontalo Province.